Superb Microvascular Imaging Compared With Power Doppler Ultrasound in Assessing Synovitis of the Knee in Juvenile Idiopathic Arthritis: A Preliminary Study. (20th June 2019) - Alis, Deniz; Erol, Burak Caglar; Akbas, Serkan; Barut, Kenan; Kasapcopur, Ozgur; Adaletli, Ibrahim
Abstract : Objectives: To investigate the efficiency of Superb Microvascular Imaging (SMI; Toshiba Medical Systems, Tustin, CA) in assessing inflammation of the synovium in the knee of patients with juvenile idiopathic arthritis (JIA) compared with power Doppler ultrasound (PDUS). Methods: Both knees of patients with a diagnosis of clinically active JIA were examined with grayscale ultrasound (US). The knees with positive US and physical examination findings were included in group A, whereas the knees with positive US findings despite negative physical examination findings were included in group B. The observers calculated the vascularity index (VI) by manually drawing a region of interest onto the thickest part of the synovium using PDUS and SMI. Results: The median SMI VI (observer 1, 4.9% [interquartile range (IQR), 3.6%]; observer 2, 4.1% [IQR, 4.6%]) exceeded the median PDUS VI (observer 1, 1.5% [IQR, 1.8%]; observer 2, 1.5 [IQR, 1.9%]; P  < .0001). In group B, the median SMI VI (observer 1, 2.85% [IQR, 8%]; observer 2, 3.1% [IQR, 6.3%]) exceeded the median PDUS VI (observer 1, 0.5% [IQR, 2%]; observer 2, 0.55% [IQR, 2.3%]; P = .002 and .001 for observers 1 and 2, respectively). No significant differences were observed between groups concerning the PDUS VI and SMI VI ( P  > .05). Conclusions: Superb Microvascular Imaging was superior to PDUS in depicting blood flow in the hypertrophied synovial tissue in the knee of patients with clinically active JIA. Superb Microvascular Imaging seems to a promising tool and a valuable adjunct to conventional US in assessing inflammation of the synovial tissue in patients with JIA.